Teaching Linguistic Segments in Multigrade Classrooms: The Case of Reading Teachers in Suyo District - Badol, Mayo T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This qualitative case study explored the experiences of multigrade teachers in teaching linguistic segments. Using purposive sampling with five criteria, multigrade teacher who graduated with a degree in Education, Linguistics, or a related field, at least three years of teaching experience as multigrade teacher, permanent teacher plantilla item, teaching in multigrade classroom, last willing to participate. The researcher gathered data from selected multigrade teachers to examine their teaching techniques, challenges, and coping strategies. Findings revealed that teachers employed varied strategies like phonics instruction, interactive learning, multisensory and communicative approaches, and contextualized methods demonstrating their adaptability. However, these techniques highlighted the need for comprehensive training to ensure effective application across diverse classroom settings. Teachers also faced significant difficulties, including limited resources, challenges in developing phonological awareness and pronunciation, and managing learner diversity. Despite this, they exhibited resilience through student-centered practices, professional development, and a positive teaching mindset. A contextualized teaching model for teaching linguistic segments was developed and validated, showing very high validity across key areas, making it a practical and effective instructional tool. Future research should expand to other regions, apply mixed-method approaches, and assess long-term effectiveness of the framework to support instructional improvement and student outcomes in multigrade linguistic teaching.